UMP goes the extra mile to assist new undergraduate Amrina - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) recently went the extra mile to help new undergraduate, Amrina Rusyada Mat Kamal, made it to campus ground in Gambang, after she was offered to enroll for a Bachelor’s Degree in Project Management at the university for the 2019/2020 intake session.